Documenting psychiatric risk: more than ticking boxes. (December 2019) - Ng, Lillian; Zeng, Irene; Kalinowski, Coni; Watson, Peter
Objective: The purpose of this study was to audit the completion of risk assessment documentation by staff working within an acute adult mental health setting. Method: Fifty risk assessment forms in a district health board's acute adult mental health service were audited for completion. Clinicians provided verbal feedback on the audit results. Results: Risk assessment forms were completed in 58.3% of cases. A risk formulation statement was completed in 43.8% of cases. Rates of completion varied between senior medical officers, registrars and nurses. Conclusion: Accurate risk formulation and safety planning are more important than ensuring all boxes are ticked on a form. Optimising the design of electronic forms may enhance access to information about historical risk.